(untitled) (DARYAFT, 2025)
This article explores the concept of mystical love in Arabic Muslim literature with special reference to Ibn al-‘Arabi’s ‘Tarjuman al-Ashwaq’. It highlights how Muslim literature, rooted in the Qur’an and Hadith, emphasizes truth, spirituality, and human refinement. Unlike secular literary traditions, Muslim poets and writers fuse artistic expression with moral and spiritual values, making literature a means of personality formation and social development. Within this framework, Ibn al-‘Arabi emerges as a towering figure who profoundly shaped Islamic mystical thought. Born in Andalusia, he is revered as al-Shaykh al-Akbar for his influential writings on Sufism and philosophy, including ‘Al-Futuhat al-Makkiyya’, ‘Fusus al-Hikam’, and ‘Tarjuman al-Ashwaq’. His doctrine of wahdat al-wujud (Unity of Being) interprets all existence as manifestations of ‘ Tarjuman al-Ashwaq’, Ibn al-‘Arabi presents his mystical experiences through symbolic and allegorical love poetry. Although critics accused him of romanticism, he clarified that his verses veil profound spiritual truths expressed through the language of love. Ultimately, his conception of love transcends the personal and embodies the eternal quest for Divine proximity, shaping Muslim literary expression and the symbolic tradition of the Urdu ghazal. Conflict of Interest: The author declares that there are no conflicts of interest related to the research, authorship, and/or publication of this article, and that the data presented have not been fabricated or falsified. Funding: This research did not receive any specific grant or financial support from public, commercial, or not-for profit funding agencies. Participant Consent: The author confirms that Informed consent was obtained from all participants, and confidentiality was duly maintained.